Dynamic analysis of the epidemiology and pathogen distribution of bronchoalveolar lavage fluid in children with severe pulmonary infection: a retrospective study - Muchun Yu; Mingchao Li; Huiqing Sun (Italian Journal of Pediatrics)
Abstract Background Severe pulmonary infection is the primary cause of death in children aged < 5 years. The early identification of pathogenic bacteria and targeted anti-infective therapies can significantly improve the prognosis of children with severe infections. This study aims to provide a reference for the rational use of antibiotics at an early stage in children with severe pulmonary infections. Methods A retrospective, single-center longitudinal study included children with severe pulmonary infections between January 2017 and December 2022 by obtaining their bacterial culture results of bronchoalveolar lavage fluid. Results This study included 4080 samples. The age of onset for severe pulmonary infection increased annually. The proportion of severe pulmonary infections across the different age groups and years was statistically significant (p < 0.001). Among children with severe pulmonary infections, bacilli were the most prevalent, followed by cocci and fungi. The predominant bacilli were Acinetobacter baumannii and Klebsiella pneumoniae. The predominant cocci identified in this study were Streptococcus pneumoniae and Staphylococcus aureus. The primary fungi included Candida albicans and Aspergillus fumigatus, which showed significant differences (p < 0.05). The incidence of drug-resistant bacteria has gradually declined, with infection rates of multidrug-resistant bacteria and extended-spectrum beta-lactamases consistently decreasing annually. For carbapenem-resistant Acinetobacter baumannii and Pseudomonas aeruginosa, the infection rates peaked in 2018, with statistical significance (p < 0.001). Conclusions Severe pulmonary infections in children are significantly associated with age and types of infectious pathogens. Gram-negative bacteria are the primary cause of severe pulmonary infections in children. Clinicians should rationally use antibiotics according to the local distribution and drug resistance of pathogens, thereby enhancing therapeutic outcomes.